Efektivitas Berbagai Media Pasir Lokal Sebagai Media Filtrasi Air Baku Menjadi Air Untuk Kebutuhan Higiene Sanitasi - Tony K Timpua; Agnes T Watung (POLTEKKES KEMENKES MANADO, 2021)
Meeting the needs of clean water services in the community requires innovation with appropriate technology by developing groundwater or well water treatment (filtering) which has a high turbidity level so that clean water is obtained with quality that meets health requirements The water processing (filtering) is the Water Well Submerged Filter by using filter media, namely sand, gravel, activated carbon, and fibers. The purpose of this study was to determine the ability of the immersed water filter to reduce water turbidity, Fe, Mn content and total coliform. This type of research is experimental with the design of One Group Pretest-Posttest Design. The results showed that the immersed water filter was effective in reducing turbidity and Fe content in the water, while the immersion filter's ability to reduce the Mn content and total coliform was not effective. It was concluded that the Up Flow Sand Filter in which A filter with sea sand media, B filter with land sand medium and C filter with sea sand media effectively reduced the turbidity and manganese levels, while the total coliform for and E. coli still exceeded the required quality standards. Further research needs to be done on the effect of varying media thickness and finer diameter in order to reduce colform and E. coli effectively